Kangaroos and other marsupials - Barrett, Norman S. (New York : F. Watts, 1991)
Examines a wide variety of marsupials, such as kangaroos, opossums, and wombats, and describes their physical characteristics, habits, natural environment, and evolution.
Includes index.
Spine title: Kangaroos.
School Library Journal.
6.4
3-5.
3-6
Keywords: Marsupialia -- Juvenile literature; Marsupials; Marsupials